Newly Revised Study of Daily Time Series Data Analysis of Market Prices - Jarrett, Jeffrey (Advances in Social Sciences Research Journal, 2022)
The purpose of this paper is to clarify the existence of time series characteristics of daily stock prices of securities marketed on organized exchanges. This study differs from previous studies where the focus was on index numbers of daily stock market prices rather than the actual prices of traded securities. Furthermore, this study is important because of the theory of market efficiency and its application to short term forecasting of closing prices of traded securities.